Hyperlipidemia in Early Adulthood Increases Long-Term Risk of Coronary Heart Disease. Issue 5 (3rd February 2015) - Navar-Boggan, Ann Marie; Peterson, Eric D.; D'Agostino, Ralph B.; Neely, Benjamin; Sniderman, Allan D.; Pencina, Michael J.
<x xml:space="preserve">Abstract</x> Background— Many young adults with moderate hyperlipidemia do not meet statin treatment criteria under the new American Heart Association/American College of Cardiology cholesterol guidelines because they focus on 10-year cardiovascular risk. We evaluated the association between years of exposure to hypercholesterolemia in early adulthood and future coronary heart disease (CHD) risk. Methods and Results— We examined Framingham Offspring Cohort data to identify adults without incident cardiovascular disease to 55 years of age (n=1478), and explored the association between duration of moderate hyperlipidemia (non–high-density lipoprotein cholesterol≥160 mg/dL) in early adulthood and subsequent CHD. At median 15-year follow-up, CHD rates were significantly elevated among adults with prolonged hyperlipidemia exposure by 55 years of age: 4.4% for those with no exposure, 8.1% for those with 1 to 10 years of exposure, and 16.5% for those with 11 to 20 years of exposure (P<0.001); this association persisted after adjustment for other cardiac risk factors including non–high-density lipoprotein cholesterol at 55 years of age (hazard ratio, 1.39; 95% confidence interval, 1.05–1.85 per decade of hyperlipidemia). Overall, 85% of young adults with prolonged hyperlipidemia would not have been recommended for statin therapy at 40 years of age under current national guidelines. However, among those not considered statin therapy candidates at 55 years of age, there remained a significant association between cumulative exposure to hyperlipidemia in young adulthood and subsequent CHD risk (adjusted hazard ratio, 1.67; 95% confidence interval, 1.06–2.64). Conclusions— Cumulative exposure to hyperlipidemia in young adulthood increases the subsequent risk of CHD in a dose-dependent fashion. Adults with prolonged exposure to even moderate elevations in non–high-density lipoprotein cholesterol have elevated risk for future CHD and may benefit from more aggressive primary prevention.